The Role of Women’s Leadership in Manufacturing Companies Listed on the Indonesia Stock Exchange - Ratieh Widhiastuti; Kiswanto Kiswanto; Kuat Waluyo Jati (The Indonesian Journal of Accounting Research, 2020)
This study aims to determine the role of women in the board of directors in increasing company value through financial performance. The research object was all manufacturing companies listed on the Indonesia Stock Exchange in 2017. The sampling technique used purposive sampling on condition that the company had a board of directors and a female commissioner and did not experience a loss during the observation year. The research data used secondary data in the form of annual financial statements which were downloaded through the official website of the Indonesia Stock Exchange (IDX). Hypothesis testing used WarpPLS analysis. The results showed that the presence of women on the board had a negative impact on financial performance, financial performance had a positive and significant effect on company value, and the presence of women on the board had a significant negative effect on company value through financial performance.